1961
DOI: 10.2136/sssaj1961.03615995002500050018x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phosphorus Fertilization on the Zinc Nutrition of Several Irrigated Crops

Abstract: In field experiments, P‐induced Zn deficiencies were observed in field corn in 1958 and in sweet corn, tomatoes and field corn in 1959. In greenhouse experiments with Red Kidney beans (Phaseolus vulgaris), severe P‐induced Zn deficiencies occurred with P fertilization. Zinc absorption was increased by Zn fertilization and decreased by P fertilization. Phosphorus uptake was increased with P fertilization and decreased by Zn fertilization. When both Zn and P were applied, the uptake of both Zn and P were reduced. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 0 publications
4
25
0
1
Order By: Relevance
“…This variability has been attributed to the differential capacity of cultivars to exploit soil Zn and translocate it to the metabolically active parts of the plant. Brown and Tiffin (1962) reported P-induced Zn deficiency in cotton, whereas Burleson et al (1961) did not observe such an effect of P on cotton. These variable findings might be associated with the different varieties used in their studies.…”
Section: Introductionmentioning
confidence: 93%
“…This variability has been attributed to the differential capacity of cultivars to exploit soil Zn and translocate it to the metabolically active parts of the plant. Brown and Tiffin (1962) reported P-induced Zn deficiency in cotton, whereas Burleson et al (1961) did not observe such an effect of P on cotton. These variable findings might be associated with the different varieties used in their studies.…”
Section: Introductionmentioning
confidence: 93%
“…It has been suggested that P fertilization induces Zn deficiency through a reaction that occurs at the root surface or within the root (Burleson et al, 1961;Sharma et al, 1968). The P-induced Zn deficiency may be a result of the increased crop growth Fageria and Zimmermann, 1979. due to P fertilization of acid soils in which the available Zn supply is marginal.…”
Section: E Zincmentioning
confidence: 99%
“…This antagonism has been explained on the basis of chemical reaction between P and Zn in the growth medium, whereby an insoluble phosphate is formed, making Zn less available to the plants. Some authors have claimed that P affects the absorption of Zn by roots in soil by some way other than precipitation of an insoluble zinc phosphate (3,4,7).…”
Section: Inthqductiokmentioning
confidence: 99%